Factor invariance of the Humor Styles Questionnaire and its relationship with the HEXACO personality model in a Spanish community sample - Đorđe Čekrlija; Ferran Balada; Luis F. Garcia; Anton Aluja (The European Journal of Humour Research, 2023)
The cross-cultural factor invariance of the Humor Styles Questionnaire (HSQ) structure, and its relationships with the HEXACO personality model were analyzed in a large Spanish community sample. The effect of age, gender, and social position on the observed relationships was also investigated. The four-factor structure of the HSQ was largely invariant compared to the original one. Males and younger participants score higher on all four domains of the HSQ, but no relevant effect of social position is observed. The HEXACO-60 dimensions and facets predicted between 17% and 32% of the HSQ domains. Results and discussion broadly support that the HEXACO personality model can be used as an adequate personality framework for the research and understanding of humor styles.